Use of Differential Evolution Algorithm for Parameter Optimization in Weather Prediction Models - Permana, Nana Yudi; Sari, Deassy Ratna Juwita (Marqcha Institute, 2023)
This research aims to optimize the parameters in a weather prediction model using the Differential Evolution (DE) algorithm, with a focus on improving the accuracy of more reliable weather predictions. The main problems faced in developing weather prediction models are model complexity and uncertainty in parameterization. The DE method is used to adjust the complex parameters in the model, resulting in a significant improvement in weather prediction accuracy based on evaluation using observational data. The implications of this research are that it makes a valuable contribution to our understanding of parameter optimization in weather prediction, as well as improving our ability to predict atmospheric conditions more accurately and reliably.